Factors influencing e-loyalty among Thai consumers in mobile food delivery applications - Sudaporn Sawmong; Navidreza Ahadi; Suwaj Dansomboon (J for Global Business Advancement, 2023)
The study investigates the key factors influencing customer e-loyalty toward mobile food delivery applications (MFDAs) in Thailand. Employing a quantitative research approach, the study collected 360 responses from MFDA users through a simple random sampling technique. The data was analysed using structural equation modelling (SEM), which revealed that factors such as trustworthiness, consumer awareness, innovative design, technology acceptance, and consumer satisfaction positively impact consumer e-loyalty. The findings confirmed significant correlations between these variables, highlighting their importance in shaping consumer e-loyalty in MFDA. The study's findings indicated that the MFDA service provider may utilise them to acquire a better understanding of the food delivery application's (FDA) customer loyalty in the future, refining their services, improving customer engagement, as well as developing marketing strategies, uncovering opportunities, and gaining a competitive edge. By leveraging these findings, companies can uncover new opportunities and gain a competitive advantage in the rapidly evolving food delivery market.
Keywords: Technology Adoption and User Behaviour